2020
DOI: 10.1002/adhm.202000392
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol‐Loaded Dual‐pH‐Sensitive Micelle Counteracts Pro‐Metastasis Effect of Paclitaxel in Triple‐Negative Breast Cancer Therapy

Abstract: The therapy of triple‐negative breast cancer (TNBC) relies on chemotherapy basing on cytotoxic agents, including paclitaxel (PTX). Unfortunately, PTX will facilitate the invasion of cancer cells and the formation of metastases. To counteract pro‐metastasis of PTX in TNBC therapy, in this work, calcitriol (CTL) is delivered along with PTX by a dual‐pH‐sensitive micelle. The PTX/CTL‐co‐loaded dual‐pH‐sensitive micelle (PCDM) can switch its surface charge from negative to positive at the tumor tissue and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In a recent preclinical study, Zheng and colleagues described a methodology to deliver paclitaxel along with calcitriol by pH-sensitive micelles, allowing for an efficient tumor uptake of the paclitaxel+calcitriol combination. This treatment suppressed primary tumor growth and inhibited lung metastasis formation in 4T1 tumor-bearing mice as a result of matrix metalloproteinase-9 (MMP)-9 and Bcl-2 level downregulation as well as E-cadherin upregulation [ 56 ]. 4T1 is an animal model for stage IV human BC.…”
Section: Calcitriol In Combination With Chemo/radiotherapy In Bcmentioning
confidence: 99%
“…In a recent preclinical study, Zheng and colleagues described a methodology to deliver paclitaxel along with calcitriol by pH-sensitive micelles, allowing for an efficient tumor uptake of the paclitaxel+calcitriol combination. This treatment suppressed primary tumor growth and inhibited lung metastasis formation in 4T1 tumor-bearing mice as a result of matrix metalloproteinase-9 (MMP)-9 and Bcl-2 level downregulation as well as E-cadherin upregulation [ 56 ]. 4T1 is an animal model for stage IV human BC.…”
Section: Calcitriol In Combination With Chemo/radiotherapy In Bcmentioning
confidence: 99%
“…They found that the nanoparticles promoted drug release under low pH conditions (pH 5.5), and exhibited an excellent anti-tumor effect on MCF-7 breast cancer cells in vitro. Zheng et al 16 confirmed that delivery of PTX by pH-sensitive micelles effectively inhibited primary 4T1 tumor growth in mice and inhibited metastasis to the lungs. The preparation of PTX into smart responsive micelles enhances its cytotoxicity to breast cancer cells, thereby increasing its antitumor effect.…”
Section: Introductionmentioning
confidence: 97%
“…have been developed for targeted drug delivery. [ 41–47 ] Among potential nanocarrier forms, we synthesized a high water dispersible and biocompatible oxygen‐rich graphene oxide nanocarrier (GO‐PCH‐g‐HPG) and incorporated our selected drugs (PTX and Cur) into it. Then, we loaded the drug‐loaded GO‐PCH‐g‐HPG nanocarrier into pullulan (Pull) nanofibers using electrospinning.…”
Section: Introductionmentioning
confidence: 99%